Sosialisasi Metode Penentuan Awal Bulan Ramadhan, Syawal, dan Dzulhijjah di Indonesia (Kecamatan Ngadirojo, Kab. Wonogiri) (Altifani : Jurnal Pengabdian Masyarakat Ushuluddin, Adab, dan Dakwah, 2024)
The socialization activity for determining the beginning of the month of Ramadan, Shawwal and Dzulhijjah in Indonesia was held on Saturday, June 17 2023 in Ngadirjo District, Wonogiri Regency. The activity was held in the Ngadirjo District Hall, Wonogiri Regency. The activity was carried out as an effort to address public anxiety about the confusion over differences in determining the start of Ramadan, Shawwal and Dzulhijjah, especially the common people.  The activity was carried out in two stages, namely the first speaker explained material about determining the beginning of the lunar month from the perspective of fiqh. The second speaker continued to present an astronomical perspective. With this activity, the takmir of mosques and religious counselors can convey to the public regarding the problems of determining the beginning of the lunar month.